Development of Educational Game Material Nomenclature of Hydrocarbons and Its Derivatives as Android-Based Chemistry Learning Media - Hanim, Fatma; Widarti, Hayuni Retno; Rokhim, Deni Ainur (Jurnal Riset Pembelajaran Kimia, 2025)
Understanding of broad and abstract concepts, especially on hy-drocarbons and their derivatives, makes it necessary to use learning media. Educa-tional game learning media is a game-based media with educational purposes that are easily accepted by students. This study aims to develop educational games on hydro-carbon materials and their derivatives and determine the feasibility of the developed media.  The method used in this study uses a 4-D model developed by S. Thiagarajan (1974). In the development of the 4-D model, there are 4 stages that are applied, including: define,  design, develop, and disseminate. However, the research and devel-opment carried out is limited to the develop due to cost and time considerations. Edu-cational game development requires software Unity Engine 2D and CorelDraw 2019 The research data were obtained from the results of media and material valida-tion and trials to students in the form of quantitative data and qualitative data.  The results of the research that have been carried out are in the form of educational games on hydrocarbon nomenclature materials and their derivatives in the form of applications that can be played on Android. The results of media validation in the developed educational game obtained an average score percentage of 77% (Decent). The results of material validation obtained an average score percentage of 79% (De-cent). The results of testing on students in all aspects obtained an average score per-centage of 89% (Very Decent).